Webinar Karya Tulis Ilmiah untuk Meningkatkan Kompetensi Menulis Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Negeri Yogyakarta - Yusuf, Arya (Faculty of Engineering, Universitas Semarang, 2026)
Writing skills are an essential ability that students must master, as they will be useful in participating in lecture activities. Writing can be a means of conveying ideas in a creative and innovative manner. The purpose of this activity is to improve the scientific writing skills of new students enrolled in 2025 at the Faculty of Social and Political Sciences, Yogyakarta State University (FISIP UNY). This activity was conducted online via Zoom meeting using the lecturer and discussion methods. This activity was joined by more than 200 new undergraduate students from the faculty. This activity was organized by the Research Student Activity Unit “Screen” FISIP UNY. It was seen that the participants were enthusiastic and excited to take part in this activity. This activity was carried out successfully and received positive responses from the participants. This activity helps students to understand the rules of writing scientific papers and is able to fosters student interest and enthusiasm in bringing up creative and innovative ideas.